Aerobic selective oxidation of methylaromatics to benzoic acids over Co@N/Co-CNTs with high loading CoN4 species. Issue 48 (26th November 2019) - Chen, Bingfeng; Li, Shaopeng; Liu, Shoujie; Dong, Minghua; Han, Buxing; Liu, Huizhen; Zheng, Lirong
Abstract : A high density of CoN4 species embedded in N-doped CNTs achieved outstanding performance for selective aerobic oxidation of methylaromatics to benzoic acids. Abstract : Selective oxidation of toluene to benzoic acid (BAC) with benign oxidant O2 is of great importance, but remains a great challenge, especially using non-noble metallic catalysts. In this work, the Co@N/Co-CNT catalyst, which was composed of atomically dispersed CoN4 species embedded in N-doped CNTs and encapsulated Co nanoparticles, was synthesized. The loading CoN4 could reach 6.4 wt%. It was found that the catalyst exhibited outstanding performance for selective aerobic oxidation of toluene to BAC without additives under solvent-free conditions. The selectivity of BAC could be as high as 91.6% at a toluene conversion of 33.5%, which is much higher than the value reported to date, including those over noble metal-based catalysts. The control experiments indicated that the main active species were CoN4 sites and the outstanding catalytic performance of Co@N/Co-CNTs can be attributed mainly to the unique properties of the CoN4 species and its high loading in the catalyst. Furthermore, the Co@N/Co-CNTs also had an excellent catalytic performance in the selective aerobic oxidation of xylenes to toluic acid derivatives.